Effectiveness of Corn Shell Activated Carbon Filters in Reducing Iron (Fe) Levels in Clean Water - Kursani, Rahmina Hidayati; A., Syarifudin; Hamzani, Sulaiman; Juanda, Juanda (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Corn husk waste often accumulates and lacks optimal management, making its use as active carbon more valuable and beneficial to society. The principle of the activated carbon processing method involves adsorbing pollutants, thereby enhancing its capacity to absorb iron levels. Researchers must create filters using corn husk-activated carbon media to lower the iron levels in clean water. The research aims to determine the effectiveness of the thickness of corn husk-activated carbon filtration media, which can reduce iron levels in clean water. The research design is a True Experiment with Pretest-Posttest and Control Group Design, incorporating four variations in activated carbon thickness and six repetitions. Variations in thickness of corn husk activated carbon are 0 cm, 5 cm, 10 cm, and 15 cm. Data analysis used the Kruskall-Wallis test. The research showed that the iron level before treatment was 1.71 mg/L. After treatment with activated carbon thicknesses of 0 cm (0%), 5 cm (67%), 10 cm (80%), and 15 cm (86%), the iron content decreased. The statistical test results obtained a p-value ≤ α (0.05), indicating that all data groups had significant differences. The public can use filters with an activated carbon thickness of more than 15 cm as an alternative for reducing iron levels in clean water.